ISSUES OF HIV/AIDS PREVENTION AMONG YOUTH AND THE FORMATION OF MEDICAL CULTURE (American Journal of Interdisciplinary Research and Development, 2026)
Human Immunodeficiency Virus (HIV) and acquired immunodeficiency syndrome (AIDS) remain among the most significant global public health challenges, particularly affecting young people. The increasing spread of HIV among adolescents and youth is closely associated with insufficient medical awareness, risky behavior, social stigma, and limited access to preventive education. This article examines the major issues related to HIV/AIDS prevention among youth and emphasizes the importance of developing medical culture as a key preventive mechanism. The study analyzes scientific literature, educational practices, and preventive strategies aimed at improving youth awareness and promoting healthy lifestyles.